Implementation of 3D conformal radiotherapy technology at the National Cancer Centre Mongolia: A successful Asia‐Pacific collaborative initiative. Issue 4 (4th June 2021) - Koh, Eng‐Siew; Gogna, Nirdosh Kumar; Minjgee, Minjmaa; Tsegmed, Uranchimeg; Gonchig, Odontuya; Vanchinbazar, Enkhtsetseg; Erdenetuya, Yadamsuren; Yap, Mei Ling; Shelton, Nikki; Ochoa, Cesar; Ceylan, Abdurrahman; Lowe, Toby; et al.
Abstract: Introduction: Mongolia has a population of 3.3 million and is classified by the WHO as a lower middle‐income country. Cancer is now a major public health issue and one of the leading causes of mortality. Within the framework of an existing national cancer control plan, the National Cancer Centre of Mongolia (NCCM) aimed to implement 3D conformal radiation planning and linac‐based treatment delivery. Methods: In 2018, an opportunity arose for collaboration between the Mongolia Society for Radiation Oncology (MOSTRO), the National Cancer Centre Mongolia (NCCM), the Asia‐Pacific Radiation Oncology Special Interest Group (APROSIG) of the Royal Australian and New Zealand College of Radiologists (RANZCR) and the Asia‐Pacific Special Interest Group (APSIG) of the Australasian College of Physical Scientists and Engineers in Medicine (ACPSEM) and radiation therapists (RTTs) from a range of Australian centres. We describe here the results to date of this collaboration. Results: Despite a number of significant technical and practical barriers, successful linac commissioning was achieved in 2019. Key factors for success included a leadership receptive to change management, stable bureaucracy and health systems, as well as a synchronised effort, regional cooperation and mentorship. Conclusion: Future directions for ongoing collaborative efforts include a continued focus on education, practical training in radiotherapy planning and delivery and postgraduate education initiatives. Radiotherapy safety and quality assurance remain an ongoing priority, particularly as technological advances are sequentially implemented.